Role of Natural plant extracts for potential Antileishmanial targets–In-depth review of the molecular mechanism: Natural plant extract – potential targets for leishmaniasis - Naik, Nidhi; Kaushal, Radhey Shyam; Upadhyay, Tarun Kumar Upadhyay; Kahrizi, Danial; Al-Najjar, Mohammad A A; Khan, Mohammad Suhail; Siddiqui, Samra (Cellular and Molecular Biology, 2022)
A group of protozoan parasites known as Leishmania species can cause a variety of chronic illnesses, ranging from self-healing lesions to fatal outcomes. Drug-resistant pathogens have become common due to the lack of safe and effective medications, which has sparked the development of new therapeutic interventions, particularly plant-based natural extracts. As a way to avoid chemotherapy's side effects, natural herbal remedies have drawn more attention. In addition to having anti-inflammatory, anticancer, and cosmetic properties, the secondary metabolites of plants, such as phenolic compounds, flavonoids, alkaloids, and terpenes, have a number of positive effects on our health. Natural metabolites such as naphthoquinone, alkaloids, benzophenones, etc. that have antileishmanial and antiprotozoal activity have been the subject of extensive research. In this review paper, it can be concluded that these natural extracts can be developed into excellent therapeutic agents against Leishmaniasis.